Effecting Change: Civil Servants and Refugee Policy in 1970s Canada - Molloy, Michael J.; Madokoro, Laura (Refuge: Canada's Journal on Refugees, 2017)
Historic transformations took place in Canada’s refugee programs in the 1970s. Through the eyes of Michael Molloy, then director of Refugee Policy in the Department of Manpower and Immigration, this article explores the political climate that led to innovations in refugee admissions and resettlement efforts as they evolved from subjective, ad hoc affairs in the immediate post-war period to integral aspects of Canada’s immigration program by the late 1970s. By considering the role of individual members of the Department of Immigration, including the visa officers stationed overseas who were responsible for determining admissions and immigration officials working in policy units in Ottawa, this article points to the important role that individuals played in delivering programs that ultimately shaped the direction of refugee admissions and resettlement in Canada and the country’s engagement with the international refugee regime.